2011
DOI: 10.3155/1047-3289.61.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Use of Satellite Data in Aiding Characterization of Particulate Air Quality in the Atlanta, Georgia Metropolitan Area

Abstract: Poor air quality episodes occur often in metropolitan Atlanta, GA. The primary focus of this research is to assess the capability of satellites as a tool in characterizing air quality in Atlanta. Results indicate that intracity PM 2.5 (particulate matter Յ 2.5 m in aerodynamic diameter) concentrations show similar patterns as other U.S. urban areas, with the highest concentrations occurring within the city. PM 2.5 and MODIS (Moderate Resolution Imaging Spectroradiometer) aerosol optical depth (AOD) have higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Considering only spring and summer seasons in our previous study (Alston et al, 2011), we found that PM 2.5 and AOD have different seasonal traits with AOD values almost doubling during the summer compared to values in the spring. Here we examine the seasonal behaviour by calculating 10-yr (if available) averages of each month for both the satellite and PM 2.5 datasets.…”
Section: Seasonal Cyclementioning
confidence: 70%
See 2 more Smart Citations
“…Considering only spring and summer seasons in our previous study (Alston et al, 2011), we found that PM 2.5 and AOD have different seasonal traits with AOD values almost doubling during the summer compared to values in the spring. Here we examine the seasonal behaviour by calculating 10-yr (if available) averages of each month for both the satellite and PM 2.5 datasets.…”
Section: Seasonal Cyclementioning
confidence: 70%
“…A recent review about the state of the field is presented in Hoff and Christopher (2009). In our earlier work, we also examined the use of satellite AOD products for air quality analysis, which lead to the development of a statistical technique for predicting air quality index values in the Atlanta metropolitan area (Alston et al, 2011). Although the above studies were mainly focused on predicting PM 2.5 from AOD for air quality applications, they did reveal some important similarities and differences in the behaviour of PM 2.5 measured near the ground and AOD retrieved from space-borne instruments.…”
Section: E J Alston Et Al: Characterization Of Aerosols Of Over a mentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite data consisting of aerosol optical depth measurements were obtained from National Aeronautics and Space Administration. Other researchers 42,43 have used AOD measurements directly to estimate PM 2.5 , (via a functional relationship between AOD and PM 2.5 ). We elected not to do so because of lack of high predictability and because of missing data due to cloud cover.…”
Section: Methodsmentioning
confidence: 99%
“…Progress is still being made to exploit space-based measurements for estimating ground-level concentrations (Al-Hamdan et al, 2009;Alston et al, 2011;Catizone et al, 2014;Christopher and Gupta, 2010). For regulatory comparisons these should be seen as complements to, rather than replacements of, the ground-based measurements.…”
Section: Particle Size and Mass Concentrationmentioning
confidence: 99%